Functional Conditions and State Of Hot Mix Asphalt Pavement and its Structure of Lithuanian Motor Roads - Kazys Petkevičius; Daiva Žilionienė; Viktoras Vorobjovas (The Baltic Journal of Road and Bridge Engineering)
The state of hot mix asphalt pavement and its structure, predetermined by the distress level, largely depends on the functional conditions. The factors predetermining the functional conditions and service life of hot mix asphalt pavement and its structure are discussed in the present article: traffic loads, local climate and weather conditions, local soils (their properties), and other local factors (soil water level and moisturizing conditions, etc.). It is shown that the state of the road pavement and its structure expressed in the distress level, the roughness of hot mix asphalt pavement strength, expressed by strength coefficient Kst, largely depends on the componential composition of the upper layer of hot mix asphalt pavement and its physical and mechanical properties. The article contains recommendations for maintaining the required state of hot mix asphalt pavement and its structure (when D ≤ 8%) and for renewal of the service life of the pavement and its structure.